Coexistence of Virulence Factors and Efflux Pump Genes in Clinical Isolates of Pseudomonas aeruginosa: Analysis of Biofilm-Forming Strains from Iran - Shahram Shahraki Zahedani; Hamed Tahmasebi; Mojdeh Jahantigh (International Journal of Microbiology)
Background. Biofilm formation and efflux pumps (EPs) correlation play a critical role in the pathogenicity and antibiotic resistance of Pseudomonas aeruginosa. In this study, biofilm formation and EP’s collaborative role in clinical isolates of P. aeruginosa infection were investigated. Methods. Eighty-six (86) P. aeruginosa isolates were collected from different clinical specimens and were confirmed using different biochemical tests. The formation of biofilm was investigated by using a crystal violet assay. Also, EP genes were identified by the PCR method. Results. Based on the results, gentamicin-resistant (n = 50, 66.29%) and ciprofloxacin-resistant (n = 61, 69.66%) strains were the most frequent and colistin (n = 1, 1.12%) and ceftazidime (n = 12, 7.86%) resistant strains were the least prevalent. Furthermore, 22 isolates (31.42%) were MDR, and 11 isolates (12.35%) were XDR strains. Also, 19 isolates (22.47%) were classified as strong biofilm, 29 isolates (21.34%) as moderate biofilm, and 3 (11.23%) isolates as weak biofilm producers. The distribution of the EP genes was as follows: mexA (n = 44, 34.83%), mexB (n = 33, 32.58%), oprM (n = 59, 29.21%), oprD (n = 61, 30.33%), tetA (n = 22, 25.58%), tetR (n = 19, 22.09%), and emrE (n = 21, 24.41%). However, there was a strong significant association between biofilm formation and EPs in P. aeruginosa. Conclusions. In this study, we suggested that the presence of a multidrug resistance efflux pump, MexEF-OprN, significantly reduced P. aeruginosa pathogenicity. In contrast, the presence of the MexAB-OprM and MexCD-OprJ pumps did not affect virulence.